DNA sequencing complements morphological identification of Chiropsoides from Nam Bor Bay, Phuket, Thailand - Phuping Sucharitakul (2018)
This study was conducted by collecting samples of the jellyfish Chiropsoides from Nam Bor Bay, Phuket, in southwest Thailand. Specimens were examined and classified using both morphological and molecular methods. Morphological study revealed that all specimens were Chiropsoides buitendijki. Tissues from the gastric saccule, pedalia, exumbrella and rhopalia were extracted and sequenced using nuclear 18s rRNA. The sequences were submitted to the National Center for Biotechnology Information (NCBI). The accession number is KJ135023.